Dissociation of cephamycin C and clavulanic acid biosynthesis by 1,3-diaminopropane in Streptomyces clavuligerus - Leite, Carla A. [UNESP]; Cavallieri, André P. [UNESP]; Baptista, Amanda S. [UNESP]; Araujo, Maria L.G.C. [UNESP] (Oxford University Press (OUP), 2015)
Streptomyces clavuligerus produces simultaneously cephamycin C (CephC) and clavulanic acid (CA). Adding 1,3-diaminopropane to culture medium stimulates production of beta-lactam antibiotics. However, there are no studies on the influence of this diamine on coordinated production of CephC and CA. This study indicates that 1,3-diaminopropane can dissociate CephC and CA productions. Results indicated that low diamine concentrations (below 1.25 g l-1) in culture medium increased CA production by 200%, but not that of CephC. Conversely, CephC production increased by 300% when 10 g l-1 1,3-diaminopropane was added to culture medium. Addition of just L-lysine (18.3 g l-1) to culture medium increased both biocompounds. On the other hand, while L-lysine plus 7.5 g l-1 1,3-diaminopropane increased volumetric production of CephC by 1100%, its impact on CA production was insignificant. The combined results suggest that extracellular concentration of 1,3-diaminopropane may trigger the dissociation of CephC and CA biosynthesis in S. clavuligerus.
Keywords: Beta-lactam antibiotics; Cculture medium; Diamine; L-lysine; Streptomyces clavuligerus